Occurrence and distribution of endocrine-disrupting chemicals in mariculture fish and the human health implications - Ismail, Nur Afifah Hanun; Aris, Ahmad Zaharin; Wee, Sze Yee; Mohmad Nasir, Hanisah; Razak, Muhammad Raznisyafiq; Kamarulzaman, Nitty Hirawaty; Tuan Omar, Tuan Fauzan (Elsevier, 2021)
The presence and distribution of endocrine-disrupting chemicals (EDCs) in the mariculture fish from Pulau Kukup, Johor of Malaysia have been studied along with the impact on human health. Six different species of mariculture fish were collected, due to their high consumption in the Asian region—especially Malaysia, to assess their levels of EDCs. The highest concentration of EDCs detected in the muscle was dexamethasone (2.37–15.84 ng/g) and (0.77–13.41 ng/g), in the liver was dexamethasone (<2.54–43.56 ng/g) and progesterone (2.23–9.78 ng/g), and in the reproductive organ are dexamethasone (<2.54–37.23 ng/g) and caffeine (0.21–18.92 ng/g). The human health risk assessment in the current study suggested that there is no potential risk to the consumer because the hazard index was below 1 (HI < 1). The present study provides information on the pollution profile of EDCs and the associated human health risk with EDCs in mariculture fish.